2022
DOI: 10.23887/paud.v10i2.49950
|View full text |Cite
|
Sign up to set email alerts
|

Media Video Pembelajaran Berbasis Proyek Pada Tema Tanaman Sub Tema Cara Bercocok Tanam Untuk Anak Usia Dini

Abstract: Penggunaan media konvensional seperti kertas, membuat pembelajaran menjadi kurang efektif. Pembelajaran yang hanya dilakukan di ruangan saja, kurang dapat memberikan pengalaman belajar yang lebih baik untuk materi tentang lingkungan. Penelitian ini bertujuan untuk mengembangkan rancang bangun, mengetahui validitas dan efektivitas dar media video pembelajaran berbasis proyek untuk anak usia dini. Penelitian pengembangan mengacu pada model ADDIE. Subjek dalam penelitian ini 1 orang ahli isi materi, 1 orang ahli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Pemanfaatan berbagai bentuk media mempunyai potensi untuk memfasilitasi transformasi yang menguntungkan, termasuk pengembangan suasana yang lebih kondusif untuk pembelajaran, penggabungan umpan balik ke dalam proses belajar mengajar, dan pencapaian hasil terbaik (Prabawati & Ambara, 2022). Versi jamak dari kata Latin "medium", yang secara harfiah berarti "perantara atau pengantar", adalah asal mula kata "media".…”
Section: Pendahuluanunclassified
“…Pemanfaatan berbagai bentuk media mempunyai potensi untuk memfasilitasi transformasi yang menguntungkan, termasuk pengembangan suasana yang lebih kondusif untuk pembelajaran, penggabungan umpan balik ke dalam proses belajar mengajar, dan pencapaian hasil terbaik (Prabawati & Ambara, 2022). Versi jamak dari kata Latin "medium", yang secara harfiah berarti "perantara atau pengantar", adalah asal mula kata "media".…”
Section: Pendahuluanunclassified
“…For this reason, various teaching models are needed to achieve maximum learning outcomes. The project-based learning model uses practical activities to present basic concepts students must learn, understand, and apply to complete a specific project (Prabawati & Ambara, 2022). This model helps students to visualize concepts, collect and interpret data, and associate theory with the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Education is a conscious and planned effort carried out by families, communities and governments, through lifelong education and training activities both inside and outside school, to enable students to fulfill their various appropriate roles in the future (Andriyani & Suniasih, 2021;Maymunah & Watini, 2021). Education as a concept is interpreted and viewed by society in an inaccurate sense, it can even be said to be wrong, so that the meaning of education is often reduced to the meaning of teaching or society often makes the meaning of education the same as teaching (Aryani & Ambara, 2021;Prabawati & Ambara, 2022). So it can be concluded that education is all conscious human effort that always exists through various processes carried out both at school and outside school throughout life for the future.…”
Section: Introductionmentioning
confidence: 99%